2011 IEEE Student Conference on Research and Development 2011
DOI: 10.1109/scored.2011.6148745
|View full text |Cite
|
Sign up to set email alerts
|

Case study of filter design in embedded systems

Abstract: The MATLAB M language provides constructs for the simple representation of functions, and has been used extensively for algorithm development and verification in embedded system design. The M language processes entire arrays simultaneously, and it is expected that design based on M can be implemented faster and with the same or higher quality as compared with design based on other languages. This paper presents a case study of a design of a filter for signal processing using M-based design flow. The results of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In this case, the data length (number of bits) was 16 bits, and the position of the decimal point (binary point) was set to 10 bits. Based on the trade-off analysis performed by applying the M-based design method, it can be concluded that the analysis results can be obtained promptly, thus reducing the amount of time required for development, and the design specifications can be verified with high accuracy [14].…”
Section: Case Study Of Fir Filter Design and Verificationmentioning
confidence: 99%
“…In this case, the data length (number of bits) was 16 bits, and the position of the decimal point (binary point) was set to 10 bits. Based on the trade-off analysis performed by applying the M-based design method, it can be concluded that the analysis results can be obtained promptly, thus reducing the amount of time required for development, and the design specifications can be verified with high accuracy [14].…”
Section: Case Study Of Fir Filter Design and Verificationmentioning
confidence: 99%